Identifikasi dan Karakterisasi Sumber Daya Genetik Tanaman Buah-Buahan Lokal di Kabupaten Tabanan - SUJANA, I KETUT ADE; SUKEWIJAYA, I MADE; WIRAATMAJA, I WAYAN (Agrotrop : Journal on Agriculture Science; Vol 6 No 2 (2016), 2016)
Identification and Characterization of Genetic Resources of Local Fruits inTabanan. The fruit is a source of vitamins and minerals that ensure the metabolic processesin the human body, some of which can also be used as medicines, cosmetics, SPA (massage)social and culture as a means to use for the material of offerings. Tabanan regency, as well asother areas in Bali has a variety of fruit but the resources still underutilized. This researchaims to identify the type of fruit genetic resources in Tabanan, profile the genetic resourcesregarding the morphology of fruit and agronomic characters, as well as to compile thegeographical spread map and diversity of fruits. Identification and characterization as well asthe distribution map is very important for the conservation, development and utilization ofgenetic resources in Tabanan Regency. The results of the research conducted in Tabanan,found 31 type and 52 subtype local fruit, with 6 different types of eminent fruit, 15 kinds ofrare fruits, 12 kinds of fruit that usually use for upakara and 4 types of fruits that are use asmedicine. Based on the results of the survey conducted in tabanan then it can be possible tocomposed 34 geographical local fruit spread map.
Keywords: fruit; Tabanan; characterization; identification